Пошаговое объяснение:
58 .∛( 8x - 1/2) = 2 - 3 ⁶√( x - 1/16 ) ;
∛( 8x - 1/2) + 3 ⁶√( x - 1/16 ) - 2 = 0 ;
2∛( x - 1/16) + 3 ⁶√( x - 1/16 ) - 2 = 0 ;
введемо змінну z = ⁶√( x - 1/16 ) , ( z ≥ 0 ) :
2z² + 3z - 2 = 0 ; D = 25 > 0 ; z₁ = - 2 < 0 ; z₂ = 1/2 ;
Отже , ⁶√( x - 1/16 ) = 1/2 ; піднесемо до 6-го степеня :
x - 1/16 = 1/64 ;
x = 1/64 + 1/16 ;
x₀ = 5/64 , тоді 8x₀ = 8 * 5/64 = 5/8 . В - дь : С ) 5/8 .
60 . √ ( 2x² - 3x + 2 ) = 4 - x ; піднесемо до квадрата :
2x² - 3x + 2 = ( 4 - x )²;
2x² - 3x + 2 = 16 - 8x + x² ;
x² + 5x - 14 = 0 ; D = 81 > 0 .
За теоремою Вієта x ₁ + x₂ = - 5 . В - дь : x ₁ + x₂ = - 5 .
Пошаговое объяснение:
2 . а ) | 0 1 x |
|- 1 0 2 | < 0 ; розписуємо цей визначник :
| 1 - 1 1 |
| 0 1 x |
|- 1 0 2 | = 0 + x + 2 + 0 + 0 + 1 < 0 ;
| 1 - 1 1 | x + 3 < 0 ;
x < - 3 . В - дь : ( - ∞ ; - 3 ) .
б ) | 2 x+ 2 - 1 |
| 1 1 - 2 | > 0 ; розписуємо цей визначник :
| 5 - 3 x |
| 2 x+ 2 - 1 |
| 1 1 - 2 | = 2x + 3 - 10( x + 2 ) + 5 - 12 - x( x + 2 ) > 0 ;
| 5 - 3 x | 2x + 3 - 10x - 20 + 5 - 12 - x² - 2x > 0 ;
- x² - 10x - 24 > 0 ;
x² + 10x + 24 < 0 ;
D = 4 > 0 ; x ₁= - 6 ; x ₂= - 4 ; xЄ ( - 6 ; - 4 ) .
В - дь : ( - 6 ; - 4 ) .